Strategic asset allocation for insurers under Solvency II - Roy Kouwenberg (2019)
© 2018, Springer Nature Limited. An important question in asset management is how solvency requirements impact the investment strategies of institutional investors. In this paper, we derive the optimal asset allocation of an insurer that minimizes its capital requirement for market risk determined with the Solvency II standard formula, subject to a target return on own funds. Solvency II is the risk-based framework for setting capital requirements of European insurance companies, in force since 2016. The solvency capital requirement is set such that the insurer’s own funds can absorb losses over a 1-year horizon with a probability of at least 99.5%. Within this framework, we analyze the properties of an optimal asset allocation for a representative European life insurance company.